PEREMPUAN DALAM ISLAM (Mensinerjikan antara Peran Sosial dan Peran Rumah Tangga) - Bahri S., Andi (AL-MAIYYAH, 2015)
Islam asserts that men are the protectors for women, the physical superiority of men and womens reproductive organs should not be understood as an excess or a shortage, but both should be directed to perform its functions in proportion. Conceptually, the humanitarian aspects and the potential possessed between men and women, there is no difference between the two. Since the beginning of creation, women occupy a position equal to men, when God commanded something to the man, it also applies to women. Conversely when God commanded something to the woman, then that too applies to men. The role of women in Islam is seen as biased, it is true if it is deemed per-individual woman, not as a mechanism for rational that must be taken if we want to create the structure of a strong family in which the relationship between men and women support each other in order to achieve a harmonious family and happy and effort to organize the relationship between men and women in society in order to etiquette awake for the realization of the noble society and the superior nation.